Combination of radiofrequency ablation and sequential cellular immunotherapy improves progression‐free survival for patients with hepatocellular carcinoma. Issue 2 (5th August 2013) - Cui, Jiuwei; Wang, Nanya; Zhao, Hengjun; Jin, Haofan; Wang, Guanjun; Niu, Chao; Terunuma, Hiroshi; He, Hua; Li, Wei
Abstract : Hepatocellular carcinoma (HCC) recurs frequently after minimally invasive therapy. The aim of our study was to observe the efficiency and safety of the combined treatment of radiofrequency ablation (RFA) with cellular immunotherapy (CIT) for HCC patients. In our study, 62 patients with HCC who were treated with radical RFA were divided into two groups: RFA alone (32 patients) and RFA/CIT (30 patients). Autologous mononuclear cells were collected from the peripheral blood and separated by apheresis, and then induced into natural killer (NK) cells, γδT cells and cytokine‐induced killer (CIK) cells. These cells were identified by flow cytometry with their specific antibodies and then were infused intravenously to RFA/CIT patients for three or six courses. The tumor recurrent status of these patients was evaluated with computed tomography or magnetic resonance imaging every 3 months after RFA. Progression‐free survival (PFS), liver function, viral load and adverse effects were examined. The results implied that PFS was higher in RFA/CIT group than that in RFA group. In RFA/CIT group, six courses had better survival prognosis than three courses. Viral load of hepatitis C was decreased in two of three patients without antiviral therapy in RFA/CIT group, but was increased in RFA group. No significant adverse reaction was found in the patients with CIT. In summary, these preliminary results suggest that combination of sequential CIT with RFA for HCC patients was efficient and safe, and may be helpful in the prevention of the recurrence for the patients with HCC after RFA. Abstract : What's new? While radiofrequency ablation (RFA) is a safe and efficient treatment for hepatocellular carcinoma (HCC), therapeutic outcomes are limited by recurrence and metastasis. Cellular immunotherapy (CIT) has emerged as a promising approach to activate immune function after RFA. Here, the authors investigated the sequential combined administration of NK cells, γδT cells, and CIK cells to HCC patients following RFA. CIT with multiple synergetic immune cells significantly reduced the risk of HCC recurrence and improved progression free survival compared to RFA alone. CIT was well tolerated and safe, potentially offering a new strategy in the prevention of post‐RFA recurrence in HCC patients.